Percepción social sobre la utilización de plástico de un solo uso en la ciudad de Yantzaza - Delgado Vivas, Jessenia Estefanía (2023)
Nowadays, the awareness about the deterioration of the planet has increased, especially due to the excessive impact in the generation of solid waste because of waste plastics, among others. Single-use plastics that cause problems for the environment and for the human health. According to how people perceive this problem depends on the changes that are made in favour of the environment, this study was carried out with the purpose of determining what is the perception that the Yantzaza citizens have regarding the use of single-use plastics, where 100 surveys were applied in person, giving as a result three indicators: environmental awareness (67 %), environmental behaviour (68 %) and environmental knowledge (57 %), which helped to determine the level of average environmental perception (64 %) existing in the city, demonstrating that more than 50 % have environmental awareness about the effects caused by plastics and they are concerned about the environmental problems caused by plastics themselves. Since 98 % of those surveyed were willing to participate in the reduction of disposables, an environmental education proposal was raised that involve students and citizens from the city of Yantzaza, with the purpose of raising awareness about the use of plastics and knowing the alternatives that exist on the market for these products. Keywords: Environmental behaviour, environmental knowledge, environmental awareness, environmental perception, environmental education.